Analysis of Lobbying and Negotiations of Sri Lanka With China Regarding The Acquisition of Hambantota Port In 2017 - Manuputty, Tessalonica; Nugroho, Agung Yudhistira (Publikasi Indonesia, 2023)
This study aims to analyze Sri Lanka's lobbying and negotiations with China through offering debt for equity swaps, i.e. exchanging debt into assets. The situation at that time was that Sri Lanka wanted to build a port on the Hambantota route, or now known as Hambantota Port. But Sri Lanka lacks funds for development and needs help from a large economy. China, which has good bilateral relations with Sri Lanka, is willing to provide assistance to Sri Lanka in the form of loans. Behind the loan lies China's national interest, which is to expand the trade route of the Belt and Road Initiative. But after the port operated, the output of the port was not optimal and even suffered losses. Gradually Sri Lanka's foreign debt is getting bigger, and it is in a cornered condition of difficulty paying debts to China, but on the other hand Sri Lanka also needs funds, namely port operational costs to continue operating. Until finally Sri Lanka nogision to China by doing debt for equity swaps with the result that China agreed to acquire the Hambantota port.